Narrative medical visualization to communicate disease data. (October 2022) - Meuschke, Monique; Garrison, Laura A.; Smit, Noeska N.; Bach, Benjamin; Mittenentzwei, Sarah; Weiß, Veronika; Bruckner, Stefan; Lawonn, Kai; Preim, Bernhard
Abstract: This paper explores narrative techniques combined with medical visualizations to tell data-driven stories about diseases for a general audience. The field of medical illustration uses narrative visualization through hand-crafted techniques to promote health literacy. However, data-driven narrative visualization has rarely been applied to medical data. We derived a template for creating stories about diseases and applied it to three selected diseases to demonstrate how narrative techniques could support visual communication and facilitate understanding of medical data. One of our main considerations is how interactive 3D anatomical models can be integrated into the story and whether this leads to compelling stories in which the users feel involved. A between-subject study with 90 participants suggests that the combination of a carefully designed narrative structure, the constant involvement of a specific patient, high-qualitative visualizations combined with easy-to-use interactions, are critical for an understandable story about diseases that would be remembered by participants. Graphical abstract: Highlights: A template to structure medical disease stories. Storyboards for three diseases that are enriched with interactive medical data visualization. A between-subject study which shows the added value of narrative medical visualization. A research agenda for narrative medical visualization.